GREEN SUKUK: FINANCING CLIMATE ACTION THROUGH ISLAMIC PRINCIPLES - Tajus Subqi; Arina Haqan; Rina Nur Janna; Muawwanah (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
Climate change poses one of the most pressing challenges of the 21st century, requiring innovative financing mechanisms to support global mitigation and adaptation efforts. This study examines green sukuk as an Islamic financial instrument that integrates environmental sustainability with Shariah-compliant principles, offering a viable pathway for financing climate action in Muslim-majority countries. The research employs a qualitative approach through systematic literature review and case study analysis of green sukuk issuances in Malaysia, Indonesia, and the United Arab Emirates from 2017 to 2025. Data were collected from regulatory documents, financial reports, and academic publications, analyzed using thematic content analysis. Findings reveal that green sukuk successfully mobilize capital for renewable energy, sustainable infrastructure, and climate resilience projects while adhering to maqasid al-shariah principles of environmental stewardship (hifz al-bi’ah). The study identifies three critical success factors: robust regulatory frameworks, standardized green certification processes, and stakeholder engagement mechanisms. Despite challenges including limited market awareness and standardization gaps, green sukuk demonstrate significant potential in bridging the climate finance gap. This research contributes to the emerging discourse on Islamic sustainable finance and provides policy recommendations for expanding green sukuk markets globally.